(untitled) - Jorgensen, Robert B. (New York, 2003)
Individually Managed Accounts: An Investor’s Guide presents the first comprehensive read on this increasingly popular investment vehicle. Through in-depth insights culled from years of experience, financial expert Robert Jorgensen fully explains what IMAs are, how they can be used, and the related pros and cons of investing in them compared to such alternatives as mutual funds. Individually Managed Accounts is the most comprehensive guide written about IMAs and explores investment options, alternatives, costs, risks, myths, and realities. This book provides step-by-step guidance and professional advice, and will show you how to select, retain, and work with an investment manager within an IMA.
Keywords: Portfolio management,Investment analysis,Quản lí danh mục đầu tư,Phân tích đầu tư